Pengaruh Substitusi Puree Labu Kuning (Cucurbita moschata) terhadap Kualitas Sensoris dan Uji Kesukaan pada Kue Nastar - Ulfah Zahra Pramono; Setyo Widiarto (Eduturisma, 2025)
This study aims to analyze the effect of pumpkin (Cucurbita moschata) puree substitution on the sensory quality and consumer preference level of nastar cookies. Pumpkin was chosen as an innovative ingredient to enhance nutritional value and optimize the utilization of local food resources. The research method employed was a true experiment with three variations of pumpkin puree substitution formulations: N2 (10%), N3 (20%), and N4 (30%). Data were collected through a hedonic test involving 74 panelists using a 1–5 Likert scale questionnaire, covering attributes of color, aroma, flavor, and texture. The results indicated that the substitution of pumpkin puree significantly influenced the sensory characteristics of the nastar. The best formulation most preferred by consumers was sample N3 (20% substitution) with an accumulative average score of 3.99 (categorized as "Liked"). Sample N3 showed excellence in flavor, aroma, and a texture that was soft yet firm, as well as an naturally appealing golden yellow color. These findings imply that using pumpkin puree up to 20% can be a viable alternative for developing healthy culinary products based on local wisdom.